From First-Release to Ex-Post Fiscal Data: Exploring the Sources of Revision Errors in the EU - Roel Beetsma; Benjamin Bluhm; Massimo Giuliodori; Peter Wierts (Tinbergen Institute, 2011)
This paper explores the determinants of deviations of ex-post budget outcomes from first-release outcomes published towards the end of the year of budget implementation. The predictive content of the first-release outcomes is important, because these figures are an input for the next budget and the fiscal surveillance process. Deviations of ex-post from first-release fiscal figures may arise for political and strategic reasons. In particular, Ministries of Finance control the production of first-release figures, and may have an incentive to be over-optimistic at this stage. Our results suggest that an improvement in the quality of institutions, whether measured by the tightness of national fiscal rules, the medium-term budgetary framework or budgetary transparency, reduces the degree of optimism at the first-release stage, thereby making first-release figures more informative about the eventual outcomes. This supports the European Commission proposals for minimum standards for national fiscal frameworks and amendments by the European Parliament for improving national ownership. It also strengthens the case for a close monitoring by the Commission of the first-release production of fiscal figures.
Keywords: E6; H6; 330; real-time data; first-release data; ex-post data; fiscal policy; biases; decomposition; base effect; growth effect; denominator effect; fiscal institutions; Finanzpolitik; Wirtschaftsindikator; Staatliche Information; Prognoseverfahren; Wirtschaftswachstum; EU-Staaten